2007
DOI: 10.1016/j.clim.2007.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Yeast glucan particles activate murine resident macrophages to secrete proinflammatory cytokines via MyD88- and Syk kinase-dependent pathways

Abstract: The therapeutic benefits of fungal beta-glucans have been demonstrated as immuno-stimulating agents. In this study, we aimed to explore the mechanisms used by yeast beta-glucan-rich particles to activate murine resident macrophages for cytokine secretion. We demonstrated that resident macrophages were effectively activated by whole yeast beta-glucan particles (WGPs), such as with the upregulation of co-stimulatory molecules and the secretion of cytokines. The binding ability of WGPs and the levels of cytokine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 36 publications
4
35
0
Order By: Relevance
“…Reishi, Shiitake and Maitake [8,9]. They are potentreticuloendothelial-modulating agents whose immunobiological activity is mediated by stimulating proinflammatory cytokine production, in part, by an increase in the number and function of macrophages [10], modulation of immunity, and resistance to microbial challenge [11]. The b-glucans can greatly increase numbers of phagocytes for phagocytosis and induce the specific receptor expression to be presented onto the cell surface [12], such as Dectin-1(b GR) and Toll-like receptors (TLR-2) [12][13][14], which recognize and bind to foreign invaders, such as microbes, viruses, yeasts, parasites, and neoplastic cells.…”
Section: Introductionmentioning
confidence: 99%
“…Reishi, Shiitake and Maitake [8,9]. They are potentreticuloendothelial-modulating agents whose immunobiological activity is mediated by stimulating proinflammatory cytokine production, in part, by an increase in the number and function of macrophages [10], modulation of immunity, and resistance to microbial challenge [11]. The b-glucans can greatly increase numbers of phagocytes for phagocytosis and induce the specific receptor expression to be presented onto the cell surface [12], such as Dectin-1(b GR) and Toll-like receptors (TLR-2) [12][13][14], which recognize and bind to foreign invaders, such as microbes, viruses, yeasts, parasites, and neoplastic cells.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that β-glucan isolated from mushroom (Shen et al, 2007), seaweed (Vetvicka et al, 2007), or Saccharomyces cerevisiae (Li et al, 2007;Yoon et al, 2008) influences the cytotoxic activity of immune cells, but β-glucan is simply showing structure of polysaccharides and contains a variety of molecules. Thus, mushrooms might have their own β-glucan.…”
Section: Discussionmentioning
confidence: 99%
“…LG Antigen presentation cells (APC) which are able to initiate innate immunity, such as macrophages, express specific surface receptors, such as Dectin-1, to recognize 1,3-β-glucan (29,30). These processed then initiated the adaptive immune responses, accompanied by the secretion of pro-inflammatory cytokines (6,30,31). In the present study, macrophages were isolated from mice treated with 1,3-β-glucan, and co-cultured with lymphocytes in vitro.…”
Section: Discussionmentioning
confidence: 99%